2016
DOI: 10.1007/s00193-016-0674-8
|View full text |Cite
|
Sign up to set email alerts
|

Viscous solution of the triple-shock reflection problem

Abstract: The reflection of a triple-shock configuration was studied numerically in two dimensions using the Navier-Stokes equations. The flow field was initialized using three shock theory, and the reflection of the triple point on a plane of symmetry was studied. The conditions simulated a stoichiometric methane-oxygen detonation cell at low pressure on time scales preceding ignition, when the gas was assumed to be inert. Viscosity was found to play an important role on some shock reflection mechanisms believed to acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Unfortunately, such investigations (Gamezo et al 2000;Mahmoudi et al 2014) have revealed that practically attainable resolutions, in full-scale two-dimensional problems, are insufficient to capture the correct reaction rates of unburned pockets. Thus, full-scale DNS is currently limited to providing insight only on single-isolated events, such as triple point collisions (Ziegler et al 2011;Lau-Chapdelaine & Radulescu 2016). Furthermore, turbulence inherently contains three-dimensional effects.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such investigations (Gamezo et al 2000;Mahmoudi et al 2014) have revealed that practically attainable resolutions, in full-scale two-dimensional problems, are insufficient to capture the correct reaction rates of unburned pockets. Thus, full-scale DNS is currently limited to providing insight only on single-isolated events, such as triple point collisions (Ziegler et al 2011;Lau-Chapdelaine & Radulescu 2016). Furthermore, turbulence inherently contains three-dimensional effects.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations will now be used to elucidate the flow field at early stages of the reflection and at higher Mach numbers. The numerical study is an extension of the work by Lau-Chapdelaine & Radulescu (2016).…”
Section: Numerical Predictionmentioning
confidence: 99%
“…The initial conditions can be recreated using the data from table 3 employing the shock Mach numbers with the Rankine–Hugoniot equations, the angles between discontinuities and the reference frame speed (post-reflection Mach stem speed, calculated using three shock theory). Using a triple shock as initial condition does away with non-physical leaky boundary conditions and provides an unambiguous way to pose the problem (Lau-Chapdelaine & Radulescu 2016). It also closely resembles triple-shock reflections in detonations.…”
Section: Numerical Predictionmentioning
confidence: 99%
See 2 more Smart Citations